Arch Structure Concept in Lightweight Fill Design - Lim Meng Siang, Alvin John (International Journal of Integrated Engineering, 2019)
Construction of road embankment over soft soils can cause significant non uniform excessive settlements that contribute to uneven road surfaces. This is due to the properties of soft soil which have low shear strength, high water content and high compressibility. These properties of soil are quite difficult and challenging to work with. This research is focused on how to mitigate the non-uniform settlement of embankments on soft soil using an innovative arch structure concept design incorporating with the current construction method of expanded polystyrene (EPS) as lightweight fill material. EPS are lightweight fill materials which are low density, stable, inert, environmentally safe fill rigid mats for road construction. However, they are large bulky blocks and have high buoyancy characteristics which will be unstable when high water table arises. The arch structure design reduces the use of EPS block while achieving almost the same performance as the conventional design. Physical modelling is used in this research to analyse the performance of this conceptual arch structure using a test box, sandy soil as embankment and wooden blocks as EPS. The concept of arch structure is implemented by removing some of the blocks at the base and setting up three different layout arrangement of spacing and thickness of the blocks which are called mixed staggering (a), mixed staggering (b) and lateral staggering. The performance of the design was measured by analyzing the settlement of the three arrangement layouts. The settlement observed was monitored photographically and measured with markings labelled on the test box. It was found that the layouts of mixed staggering (b) have is proven to reduce the excessive non-uniform settlements compared to the lateral staggering and mixed staggering (a). Hence, this research has established a suitable design guide using a mixed staggering arch structure fill material which is light and strong to withstand heavy loading to reduce ground settlement.